2021
DOI: 10.1002/pits.22528
|View full text |Cite
|
Sign up to set email alerts
|

Returning to teaching during COVID‐19: An empirical study on elementary teachers' self‐efficacy

Abstract: The purpose of this study was to explore how the new teaching approaches and requirements because of COVID‐19 impacted elementary teachers' self‐efficacy, specifically instructional and engagement efficacy. The current study included 329 participants from across the United States who completed the Teacher Sense of Self‐Efficacy Scale (TSES) subsections of instructional and engagement. The results found the average teacher efficacy scores for both instructional and engagement were lower than TSES scores of inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 30 publications
3
44
2
3
Order By: Relevance
“…Raily et al points to similar dependencies, that high self-efficacy is an important determinant of job satisfaction among Irish teachers ( Reilly, Dhingra & Boduszek, 2014 ). Considering the COVID-19 pandemic and the new challenges for teachers related to it, their sense of self-efficacy can be an important factor determining the entire area of the teacher’s work, taking into account the sense of job satisfaction and the risk of developing professional burnout ( Pressley, 2021a ; Hoang et al, 2020 ; Pressley, 2021b ). The review of available publications shows that teachers during COVID-19 showed significantly lower self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Raily et al points to similar dependencies, that high self-efficacy is an important determinant of job satisfaction among Irish teachers ( Reilly, Dhingra & Boduszek, 2014 ). Considering the COVID-19 pandemic and the new challenges for teachers related to it, their sense of self-efficacy can be an important factor determining the entire area of the teacher’s work, taking into account the sense of job satisfaction and the risk of developing professional burnout ( Pressley, 2021a ; Hoang et al, 2020 ; Pressley, 2021b ). The review of available publications shows that teachers during COVID-19 showed significantly lower self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the teachers' lack of a clear range of strategies for interventions and management, which in turn may be explained by this never-before experienced situation of long-term online distance teaching. It seems that the teachers, lacking a clear representation of possible alternative teaching and relational strategies, failed to assess the potential solutions to this challenging teaching environment [26,27,[56][57][58]. Moreover, the data on scores on these self-related dimensions (self-esteem and self-efficacy for instructional strategies) points to a possible negative development, namely the failure to form positive and constructive coping responses and the inability to find possible active solutions to frustrating tasks or predicaments.…”
Section: Discussionmentioning
confidence: 99%
“… Dussault et al (2004) investigated the relationship between teachers’ IE and their efficacy toward integration of technologies in the classroom. Pressley (2021b) showed that teachers teaching virtually had the lowest IE scores compared with teachers teaching in a hybrid or all in-person model. In this study, PIE-OT is taken as a research variable, which reflects a teacher’s beliefs in his/her capacity in executing OT, using auxiliary media, and designing new instruction materials for e-learning.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%